Involuntary Psychiatric Admission: Arbitrary Deprivation of Liberty or a Human Right? - Tamai, Sergio (Frontiers in Psychiatry, 2022)
In 2008 Brazil ratified The United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD)1 an interna¬tional legal instrument specifically tai¬lored to stipulate the rights of persons with disabilities and include those with serious mental dis¬orders. United Nations Committee set up to monitor the implementation of the Convention (CRPD Committee) lead to an insistence that involuntary detention and treatment of people with mental health (or “psychosocial”) disabilities are pro¬hibited. There is a debate about this topic that poses an impossibility of involuntary psychiatric admission in hospital. Prohibition of involuntary treatment in patients with impaired decision-making capacity might be denial of a possibility of treatment.